PENGARUH PEMANFAATAN LIMBAH CANGKANG TELUR AYAM SEBAGAI BIOFERTILIZER TERHADAP PERTUMBUHAN KACANG TANAH (Arachis hypogaea L.) - Febi Permata Jingga; Azwir Anhar (Universitas Cokroaminoto Palopo, 2026)
This research explores the potential of chicken eggshell waste as an alternative biofertilizer to reduce dependence on synthetic chemical fertilizers, which often trigger land degradation. The main focus of this study was to analyze the extent to which eggshell powder application affects the vegetative phase of peanut (Arachis hypogaea L.) plants, while also determining the most responsive application dose. The experiment was conducted with a four-stage treatment design: P0 (control), P1 (133.3 g/polybag), P2 (200 g/polybag), and P3 (266.6 g/polybag). Parameters observed included plant height dynamics and leaf productivity. The results showed that the integration of eggshell biofertilizer significantly stimulated plant growth compared to the control. The P3 dose (266.6 g/polybag) was identified as the most effective treatment, with an average plant height of 26 cm and 32 leaves at the end of the observation period. Interestingly, at the intermediate dose (P2), there was evidence of inhibition of stem elongation despite the high leaf count. This phenomenon is thought to be related to nutritional imbalances caused by excess calcium (Ca), which inhibits the absorption of other essential micronutrients. Overall, this study confirms that the use of eggshell waste not only serves as a natural source of calcium carbonate (CaCO₃) for soil pH stabilization but is also effective in sustainably improving the agronomic performance of peanuts.